CLINICAL VERSUS C.T. SCAN DIAGNOSIS IN STROKE-A COMPARATIVE STUDY OF 50 CASES - Rehman, Shams -ur-; Khan, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2002)
Background: Cerebrovascular disease is one of the three leading causes of death in the world along with cancer and heart disease. Differentiation between cerebral infarction and intracerebral haemorrhage is important because now a days proper management of the acute stroke syndrome is based on the correct diagnosis of the pathological type. This study compared clinical and C.T. scan diagnosis of stroke and determined the reliability of the clinical diagnosis in cases of stroke. Methods: This study was conducted on 50 patients of stroke at Postgraduate Medical Institution, Lady Reading Hospital, Peshawar from Jan 1995 to May 1996. Clinical diagnoses were made in conformity with criteria for clinical diagnosis of intracranial haemorrhage, cerebral infarction due to embolism or thrombosis. The clinical diagnosis was then compared with the CT diagnosis. Results: We found that from careful history and clinical examination differentiation could be made between cerebral infarction and haemorrhage. In our study at Government Lady Reading Hospital, cerebral hemorrhage accounted for 42 % of cases of stroke and cerebral infarction in 58%. Conclusions: In order to make a clinical diagnosis of stroke, a detailed history and thorough clinical examination is mandatory. As far as treatment planning is concerned clinical diagnosis of stroke is not safe enough as a guide for anticoagulant or thrombolytic therapy. In order to confirm the aetiological diagnosis of stroke one must rely on C.T. scan examination.